患者適合型体内固定用プレート (TruMatch Reconstruction system®) を用いた下顎再建 - 新山, 宗; 上田, 倫弘; 林, 信 (日本口腔外科学会雑誌, 2024)
After continuous disarticulation of the mandible, reconstruction with a free osteocutaneous flap with vascular is effective. However, problems such as occlusal deviation 16.7％ (4/24) and facial deformity 8.3％ (2/24) may occur in the medium- to long-term course. In particular, when the muscle process and mandibular nucleus are resected and the proximal residual bone is small, dislocation is likely to occur, and intraoperative positioning of the jaw is not only difficult, but also tends to change over time. 　The TruMatch Reconstruction system is a new system that has become available in Japan due to the development of surgical simulation software and the progress of 3D printers. This system is not only accurate in mandibular reconstruction, but also enables accurate resection of tumours according to the preoperative plan by using a cutting guide. It also reduces operative time and blood loss, and is considered to be an effective item for mandibular reconstruction. 　However, there are issues that need to be improved in the future, such as the low degree of freedom of the plate and the long time between planning and completion of the product.